Equilibria in Second Price Auctions with Private Participation Costs - Xiaoyong Cao; Guofu Tan; Guoqiang Tian; Okan Yilankaya (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
We study equilibria in second price auctions when bidders are independently and privately informed about both their values and participation costs and their joint distributions across bidders are not necessarily identical. We show that there always exists an equilibrium in this general setting with two dimensional types of ex ante heterogeneous bidders. We provide conditions under which the equilibrium is unique. Moreover, when the bidders are ex ante symmetric, we show that there is a unique symmetric equilibrium. We also identify sufficient conditions for existence of asymmetric equilibria.
Keywords: C62; C72; D44; D61; D82; 330; Two-Dimensional Types; Private Participation Costs; Second Price Auctions; Existence and Uniqueness of Equilibrium